If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(t) + -20 = 33 Reorder the terms: -20 + 7t = 33 Solving -20 + 7t = 33 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 7t = 33 + 20 Combine like terms: -20 + 20 = 0 0 + 7t = 33 + 20 7t = 33 + 20 Combine like terms: 33 + 20 = 53 7t = 53 Divide each side by '7'. t = 7.571428571 Simplifying t = 7.571428571
| -14=10-2x | | 8z+12z=5z-21 | | 3x+x+4=8x-4x+4 | | 5(w+4z)-5(w+3)=8 | | 4+6r-r=-5+8r | | x+9=-17 | | 10x+x=196 | | (1/4)(p)+6=8 | | 6x+39x-7=9(5x+6) | | 4x-10=14+x | | 35=7(z)-7 | | 8(n)+16=24 | | 8.2x-2.1x=-122 | | 2(x+5)=4x+6-2x+4 | | 9x=2.25 | | -8=3(y)-2 | | 5(h)-13=12 | | 12x^3=27x^2+15x | | 6k-1-7=10 | | 7x-2=5x+8 | | 6=42-5q-q^2 | | 3x-1/(2)=10 | | -6a-5a=11 | | 3x-1/2=10 | | 2=3(a)+8 | | (3x^2+7x-20)/(x+5) | | graphy=.5x+.5 | | -8x-3x=11 | | 9x+15x-8=6(4x+5) | | -3(d)+10=43 | | t+6t+9=0 | | -2=1+6x-3x |